2011
DOI: 10.1186/1749-799x-6-17
|View full text |Cite
|
Sign up to set email alerts
|

Is surgical intervention more effective than non-surgical treatment for carpal tunnel syndrome? a systematic review

Abstract: BackgroundCarpal tunnel syndrome is a common disorder in hand surgery practice. Both surgical and conservative interventions are utilized for the carpal tunnel syndrome. Although certain indications would specifically indicate the need for surgery, there is a spectrum of patients for whom either treatment option might be selected. The purpose of this systematic review was to compare the efficacy of surgical treatment of carpal tunnel syndrome with conservative treatmentMethodsWe included all controlled trials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
0
15

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(102 citation statements)
references
References 23 publications
2
81
0
15
Order By: Relevance
“…Even so, the complication and side effects of CTR were more considerable as well. Altogether, they concluded that since conservative management is effective in relieving symptoms in a certain proportion of cases and can avoid the complications of the surgery, it remains a justified first line treatment (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even so, the complication and side effects of CTR were more considerable as well. Altogether, they concluded that since conservative management is effective in relieving symptoms in a certain proportion of cases and can avoid the complications of the surgery, it remains a justified first line treatment (8).…”
Section: Discussionmentioning
confidence: 99%
“…Conservative options for CTS treatment include splinting, nonsteroidal anti-inflammatory drugs (NSAIDs), local steroid injection (LSI), and systemic steroids. Surgical treatment of CTS includes surgical decompression through carpal tunnel release (CTR), which is usually applied for patients with progressive and persistent signs and symptoms, especially the thenar atrophy (8).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, high levels of complications were observed in both groups (57% in group allocated to surgery, 52% in non-surgical group). (Shi and MacDermid, 2011) The authors noted large variation as some studies reported all complications while others only reported clinically important adverse events. Overall pooled results indicated that non-surgical treatment for CTS was associated with fewer complications than surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In their discussion of the results, the authors concluded that given the treatment differential and potential for adverse effects and that conservative interventions benefitted a substantial proportion of patients, current practice of a trial of conservative management with surgical release for severe or persistent symptoms is supported by evidence. (Shi and MacDermid, 2011) In the current study we used BCTQ to evaluate the patient progress regarding neurogenic symptoms and functional disability. Manyauthors consider BCTQ reliable and valid methods in dealing with CTS.…”
Section: Discussionmentioning
confidence: 99%
“…However, RICE has proved less efective for treatment of pain associated with chronic overuse-MSDs than NSAIDs. Splinting for carpal tunnel syndrome is less efective than surgical release or injections of steroids around the nerve [19][20][21][22][23][24], which are also not always efective [19][20][21][22][23][24].…”
Section: Current Treatments For Overuse-msdsmentioning
confidence: 99%